C3 A RARE AND ATYPICAL CASE OF ICD POCKET HEMATOMA CONTAINING PSEUDOCHYLOUS. (18th May 2022) - Maffè, S; Paffoni, P; Bergamasco, L; Facchini, E; Prenna, E; Careri, G; Franchetti Pardo, N; Paino, A; Dellavesa, P
Abstract: Subcutaneous hematoma is a complication in 2–9% of cardiac device implants.In most cases, it is drained or spontaneously reabsorbed; if untreated, there is a risk of infection.While cases of chylothorax and pseudochylothorax are rare, no previous cases of accumulation of chyliform material in the subcutaneous pockets of cardiac devices have ever been documented.We present the case of a 60–year–old man with antibody syndrome antiphospholipids, rheumatoid arthritis, previous acute anterior myocardial infarction and aorto–coronary by–pass surgery, paroxysmal atrial fibrillation, in oral anticoagulant therapy. In 2020, the patient underwent primary prophylactic dual–chamber ICD implantation (EF 33%) at another center, complicated by the formation of a large pocket hematoma, which required drainage and evacuation. In the following weeks, the patient noticed the reappearance of a large swelling in the ICD pocket; however, as it was painless and not troublesome, he did not seek medical attention. After 7 months he came to our observation with signs of heart failure. Clinical examination revealed a large swelling in the left pectoral area (Fig. 1 ), extending to the nipple, soft, not painful, not hot or red.The patient had no signs of infection (normal ESR, CRP, procalcitonin and WBC). We decided to drain the hematoma, given the size. At the level of the defibrillator pocket, we made a small incision, from wich 100ml of gold–colored, odorless liquid leaked out (Fig. 2 ), with no evidence of blood material in the pocket. The ICD–case was then wrapped in a rifampicin–releasing antibacterial bag and reinserted into the subcutaneous pocket, without further complications. The chemical–physical examination revealed a cloudy, gold–colored liquid, density of 1020, pH 8.5, high protein content (>400g/l), absence of glucose.Microscopic examination shows isolated leukocytes, rare erythrocytes immersed in mucoid material; this was not pus, as culture testing was negative for bacterial growth. The cholesterol concentration was 704mg/dl, triglycerides 80mg/dl (plasma cholesterol values were 91mg/dl, triglycerides 48mg/dl). The cytological analysis showed a carpet of foamy macrophages filled with cholesterol crystals (Fig. 3 ). Such evidence supports the diagnosis of pseudochilous, formed from the evolution of an untouched hematoma in a fibrous subcutaneous pocket for more than 6 months.This is the first case in which the presence of chyliform material is documented in an ICD pocket.